ANALYSIS OF FACTORS AFFECTING STOCK PRICES (Case Study On PT. Telekomunikasi Indonesia (Persero) Tbk Listed On IDX Year 2016-2020) - Sulistiyowati, Lia Budi; Pitri, Selfa Benika; Rofiah, Zakiatur; Safitri, Nabilah (Universitas Mercu Buana, 2022)
This study aims to determine and analyze the effect of Earning Per Share (EPS), Price Earning Ratio (PER) and Debt to Equity Ratio (DER) on the stock price of the company PT. Telekomunikasi Indonesia (Persero) Tbk is listed on the IDX for the 2016-2020 period, either simultaneously or partially. The sample of the population used is a PT Telecommunications company for the 2016 – 2020 period. This study uses multiple linear regression analysis to see the effect of the independent variable on the dependent variable. The results showed that simultaneously, showing that Earning Per Share (EPS), Price Earning Ratio (PER) and Debt to Equity Ratio (DER) had no significant effect on stock prices at PT. Telekomunikasi Indonesia (Persero) Tbk which is listed on the Indonesia Stock Exchange for the 2016-2020 period. While partially shows that Earning Per Share (EPS), Price Earning Ratio (PER) and Debt to Equity Ratio (DER) have no significant effect on stock prices at PT. Telekomunikasi Indonesia (Persero) Tbk which is listed on the Indonesia Stock Exchange for the 2016-2020 period.